Female crickets assess relatedness during mate guarding and bias storage of sperm towards unrelated males. (21st March 2013) - Tuni, C.; Beveridge, M.; Simmons, L. W.
Abstract Recent evidence shows that females exert a post‐copulatory fertilization bias in favour of unrelated males to avoid the genetic incompatibilities derived from inbreeding. One of the mechanisms suggested for fertilization biases in insects is female control over transport of sperm to the sperm‐storage organs. We investigated post‐copulatory inbreeding‐avoidance mechanisms in females of the cricket Teleogryllus oceanicus. We assessed the relative contribution of related and unrelated males to the sperm stores of double‐mated females. To demonstrate unequivocally that biased sperm storage results from female control rather than cryptic male choice, we manipulated the relatedness of mated males and of males performing post‐copulatory mate guarding. Our results show that when guarded by a related male, females store less sperm from their actual mate, irrespective of the relatedness of the mating male. Our data support the notion that inhibition of sperm storage by female crickets can act as a form of cryptic female choice to avoid the severe negative effects of inbreeding.